CALLISTO facilities in Peru: spectrometer commissioning and observations of type III solar radio bursts - Alonso Rengifo, Javier (2021)
The Astrophysics Directorate of CONIDA has installed two radio spectrometer stations belonging to the e-CALLISTO network in Lima, Peru. Given their strategic location near the Equator, it is possible to observe the Sun evenly throughout the whole year. The receiver located at Pucusana, nearby the capital city of Lima, took data from October 2014 until August 2016 in the metric and decimetric bands looking for radio bursts. During this period, this e-CALLISTO detector was unique in its time-zone coverage. To asses the suitability of the sites and the performance of the antennas, we analyzed the radio ambient background and measured their radiation pattern and beamwidth. To demonstrate the capabilities of the facilities for studying solar dynamics in these radio frequencies, we have selected and analyzed type III Solar Radio Bursts. The study of this kind of burst helps to understand the electron beams traversing the solar corona and the solar atmospheric density. We have characterized the most common radio bursts with the following mean values: a negative drift rate of -25.8 +/- 3.7 MHz s(-1), a duration of 2.6 +/- 0.3 s and 35 MHz bandwidth in the frequency range of 114 to 174 MHz. In addition, for some events, it was possible to calculate a global frequency drift which on average was 0.4 +/- 0.1 MHz s(-1).